The future of bottle recycling in the United States of America - Koivisto, Jyri (2012)
In this Master’s thesis, the future of bottle recycling in the United States of America will be examined through interest, incentive and an infrastructure (iii) model. One of the American ways to recycle bottles, namely, the Dream Machine initiative, will be compared to the Finnish bottle recycling system. It will shed light through surveys done from Finnish high school students and randomly selected Americans about bottle recycling behaviour. In addition, two supportive surveys were administered to bring validity about the possible behavioral change through properly implemented recycling systems. The main conclusion is that through a proper implementation of a bottle recycling system, American’s behavior can change towards a more sustainable future.